Upaya Preventif Hipertensi melalui Kegiatan Edukasi GERMAS (Gerakan Masyarakat Hidup Sehat) pada Lansia: Pengabdian Masyarakat di Baguntapan, Bantul, Daerah Istimewa Yogyakarta - Rahmahdhani, Andini; Rosmawati, Elly; Permatasari, Puput Septian; Sofiana, Liena (Jurnal SOLMA, 2025)
Background: Hypertension is a non-communicable disease with a high prevalence, particularly among the elderly, and is a leading cause of death in Indonesia. Bantul Regency is among the regions with a high incidence of hypertension, thus requiring community-based promotive and preventive interventions. Methods: This community service activity was conducted on February 21, 2020, in Modalan Hamlet, Banguntapan District, Bantul. The target participants were 39 pre-elderly and elderly individuals. The program consisted of two main stages: (1) blood pressure screening and health education on the Healthy Living Community Movement (GERMAS), and (2) anti-hypertension exercise as a form of physical intervention. The education covered the definition, risk factors, complications, and prevention strategies for hypertension. Results: Most participants were found to have high blood pressure. The health education session received a positive response, with active engagement from participants. The anti-hypertension exercise was conducted collectively and was well accepted by the elderly. This intervention effectively increased participants' knowledge and awareness regarding healthy lifestyles and the importance of regular blood pressure monitoring. Conclusions: The combination of health education on GERMAS and anti-hypertension exercise effectively improved awareness and promoted healthy behavior among the elderly. This intervention is a valuable strategy for hypertension prevention at the community level.